Quality of Life in Inflammatory Bowel Disease: Psychometric evaluation of an IBDQ cross-culturally adapted version - Verissimo R. (2008)
The health related quality of life (HR-QoL) construct was introduced as a requirement to assess the subjective health status. It is a multifaceted construct that has been recognized to contribute for a better understanding of the patients' adaptation to his condition. The Inflammatory Bowel Disease Questionnaire (IBDQ), a widely used instrument to asses QoL among IBD patients, has already shown its validity and reliability. Our aim was to get a light-footed revised version of the IBDQ and to investigate its cross-cultural psychometric properties.Carried out in a sample of outpatients recruited in a specialized University Clinic (n = 76), this study began with the translation and linguistic validation of a self-report 32-item version of the questionnaire with a 7-point Likert type answering system. Just to assess thereafter its reliability through internal consistencies; and also looking into its discriminatory power. Furthermore we also investigated its convergent validity with other health status - clinical assessment, SCDAI and CDAI-m - and well-being measures. With a Cronbach's alpha = 0.92 for the global scale and a mean 0.82 for the subscales, internal consistencies proved rather adequate. On the other hand, discriminatory power was also significantly according to the model. Moreover, the expected correlations between IBDQ and the clinical assessment, SCDAI, CDAI-m and perception of well-being support evidence of IBDQ-R's convergent validity.This IBDQ revised version is a highly promising instrument to easily, yet feasibly and comprehensively assess Quality of Life in Inflammatory Bowel Disease; therefore its use in daily practice is worthy of recommendation.